THE CONCEPT OF CRYPTOCURRENCY IN ISLAM - Achmad Fajaruddin; Dimas Fahmi Azizy; M. Ridhauli Pasha Parojai; Indra Sholeh Husni; Muhamad Kharis Tambusai (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2023)
Digital money obtained by converting physical money into digital is often used in electronic transactions. However, modern technology has also produced virtual currencies, known as cryptocurrencies. Bitcoin and other cryptocurrencies are unregulated and have not received official approval by Indonesian law. Research to know and analyze the concept of crypto according to Islam. With the method of literature review combined with bibliometric analysis. Data was collected using Publish or Perish (PoP) software from the Google Scholar database. Table 1 shows the number of author citations for works discussing cryptocurrencies and Islamic studies. Based on search results obtained by PoP software. The number of citations from authors who have more than 10 citations is calculated from the total number of authors. Use keywords as a foundation. Nine clusters were found as a result of keyword mapping: red, blue, yellow, green, purple, orange, brown, and pink.